Comparison of ocular biometry and refractive outcomes using two swept-source optical coherence tomography-based biometers. - Hansol Park; Young-Sik Yoo; Eunhae Shin; Won Seok Song; Yeokyoung Won; Tae-Young Chung; Dong Hui Lim (PLoS ONE)
Background To evaluate the ocular biometry agreement and prediction of postoperative refractive outcomes obtained using two swept-source optical coherence tomography (SS-OCT) biometers: Anterion (Heidelberg Engineering, Heidelberg, Germany) and Argos (Alcon, Fort Worth, TX, USA). Methods Ambispective analysis was conducted on 105 eyes at the Samsung Medical Center, Seoul, Republic of Korea, between June 2021 and March 2022. Biometric values were assessed using both devices before cataract surgery. Intraocular lens (IOL) power, mean arithmetic error (ME), and mean absolute error (MAE) were calculated using the Barrett Universal II, Haigis, and Hoffer Q formulas. Results Anterion showed statistically significantly greater axial length (AL), central corneal thickness (CCT), and lens thickness (LT) than Argos (p = 0.03, p < 0.001, and p = 0.032, respectively). There were no significant differences in measuring anterior chamber depth (ACD) (p > 0.05). Anterion showed flatter corneal curvature measurements than Argos (p < 0.001). The postoperative prediction errors differed for all three formulas (p < 0.001). Anterion results leaned towards a slightly myopic outcome due to hyperopic target refraction. In all three formulas, the MAE and percentage of eyes with a prediction error ≤ ± 0.5 D were not significantly different between the two devices. Conclusion Although the differences are not clinically significant, the measurements of AL, CCT, and LT obtained with Anterion were greater compared to those measured with Argos, while the keratometry (K) and corneal diameter (CD) values were smaller. Consequently, this resulted in a minor difference in refractive predictability, with Anterion showing a slight tendency toward more myopic refractive errors. However, there were no significant differences in MAE or the percentage of eyes within ± 0.5D.